Efektivitas Pelaksanaan Peraturan Menteri Dalam Negeri Nomor 15 Tahun 2021 Tentang Pemberlakuan Pembatasan Kegiatan Masyarakat Darurat Covid-19 di Dinas Perhubungan, Kelautan dan Perikanan Kabupaten Jembrana - Ni Komang Sutha Yudiansari; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Fakultas Hukum Universitas Warmadewa, 2022)
Jembrana is a district located at the West end of the island of Bali. The job of the Transportation Office is to conduct transportation or transportation policies in Jembrana Regency. Soaring cases of the Covid-19 pandemic led the government to issue the Ministry of Home Affairs regulation No. 15 of 2021 so it is mandatory to implement restrictions on people's activities. The formulation of the problem discussed is: What is the effectiveness of the implementation of Ordinance No. 15 of 2021 on Enforcement of Restrictions on Covid-19 Emergency Community Activities at Jembrana District Transportation, Oceans and Fisheries Office? And How is the government's policy on regulating land travel transportation during the period of the enforcement of the Covid-19 Emergency Community Activity Restriction in Jembrana District Transportation, Oceans and Fisheries Office. This research method uses empirical research types. The effectiveness of implementing the Enforcement of Restrictions on Community Activities has been in accordance with the Ministry of Home Affairs Regulation No. 15 of 2021 that applies to the Transportation Office and Jembrana Regency areas. The government's policy of regulating land-travel transportation is to initialize passengers and compulsory PCR tests and vaccinations.